2018
DOI: 10.1136/bjophthalmol-2018-313322
|View full text |Cite
|
Sign up to set email alerts
|

Collateral vessels on optical coherence tomography angiography in eyes with branch retinal vein occlusion

Abstract: AimsTo detect collateral vessels using optical coherence tomography angiography (OCTA) in eyes with branch retinal vein occlusion (BRVO) and to investigate the associations with visual outcomes and macular oedema.MethodsEyes with macular oedema secondary to BRVO that underwent OCTA at baseline and were followed up for more than 6 months were enrolled. The presence of collaterals, whether the collaterals were leaky or not, and the associations with visual outcomes and macular oedema were investigated.ResultsTwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 28 publications
2
38
1
Order By: Relevance
“…Collateral vessels in RVO develop because of the changed hemodynamic and increased hydrostatic pressure and appear as tortuous vessels in the retina or within the optic disc and are more frequently observed in eyes with ischemic BRVO [10,27]. Our study could not show any significant differences in vascular collaterals between DR and RVO groups or correlation with BCVA.…”
Section: Plos Onecontrasting
confidence: 56%
“…Collateral vessels in RVO develop because of the changed hemodynamic and increased hydrostatic pressure and appear as tortuous vessels in the retina or within the optic disc and are more frequently observed in eyes with ischemic BRVO [10,27]. Our study could not show any significant differences in vascular collaterals between DR and RVO groups or correlation with BCVA.…”
Section: Plos Onecontrasting
confidence: 56%
“…Studies have shown that compensatory capillary modeling occurs in the brain following ischemic injury, 63,64 and in the retina following branch retinal vein occlusion. [65][66][67] We also found a lower frequency of pathways connecting the SCP to the RPCP in eyes with NPDR and this change may FIGURE 7. Patterns of capillary outflow of the SCP.…”
Section: Discussionmentioning
confidence: 91%
“…In venous occlusive diseases, such as central and branch retinal vein occlusions, OCTA can identify areas of non-perfusion as well as collateral vessel formation [80,81]. Manual slab selection provides information regarding the affected retinal vascular layers and the location of new collateral vessels.…”
Section: Octa and Other Pathologiesmentioning
confidence: 99%